Evolution of Oxygen Deficiency Center on Fused Silica Surface Irradiated by Ultraviolet Laser and Posttreatment - Hai-Bing Lü; Shi-Zhen Xu; Hai-Jun Wang; Xiao-Dong Yuan; Chao Zhao; Y. Q. Fu (Advances in Condensed Matter Physics)
Evolution of oxygen deficiency centers (ODCs) on a fused silica surface irradiated using a 355 nm ultraviolet (UV) laser beam in both vacuum and atmospheric conditions was quantitatively studied using photoluminescence and X-ray photoelectron spectroscopy. When the fusedsilica surface was exposed to the UV laser in vacuum, the laser damage threshold was decreased whereas the concentration of the ODCs was increased. For the fuse silica operated under the high power lasers, creation of ODCs on their surface resulted from the UV laser irradiation, and this is more severe in a high vacuum. The laser fluence and/or laser intensity have significant effects on the increase of the ODCs concentration. The ODCs can be effectively repaired using postoxygen plasma treatment and UV laser irradiation in an excessive oxygen environment. Results also demonstrated that the “gain” and “loss” of oxygen at the silica surface is a reversible and dynamic process.